(untitled) (Plant Bulletin, 2025)
Brassica crops including cabbage and cauliflower are extremely crucial to food security but are extremely susceptible to bacterial diseases like Xanthomonas campestris pv. campestris (Xcc) and Pseudomonas syringae pv. maculicola (Psm) that drastically lower yield and quality. Even traditional chemical pesticides, popular in use, are too dangerous to human health and the environment because of the accumulation of residues. This paper was an evaluation of the effectiveness of neem (Azadirachta indica) leaf extract as an effective alternative to the use of chemicals. Gel diffusion laboratory tests established that the neem extract, especially the 75% one, was effective in preventing bacterial growth, whereby Xcc was more suppressed than Psm. Field trials showed that neem treatment at the Economic Threshold Level (9% disease incidence) was effective in reducing disease severity and disease incidence and keeping crop healthy with minimal losses in yield. Neem has potential as an environmentally friendly biopesticide due to its biodegradability, no toxicity, and no residue effects. This body of evidence highlights the potential of A. indica in the management of diseases integrated together with its potential in enhancing sustainable production of Brassica.